Использование стратегий критического мышления для формирования мыслительной деятельности младших школьников - Гавриляк, И.М. (My University, 2016)
The renewal of the content of education encourages teachers to find effective educational strategies motivating students to perform mental activity. This article reveals the key ideas of the development technology of critical thinking as a new type of thinking characterized by flexibility, reflexivity, independence of judgment, variability of decisions. The author analyzes her own experience in realization of critical thinking strategies for the formation of functional skills, reflects on the benefits and barriers of implementing this technology at lessons in primary school.
Keywords: critical thinking; strategies; dialogue; reflexivity; interactivity